ANALISIS PEMAHAMAN KONSEP SISWA PADA MATERI PERSAMAAN KUADRAT DI SMP KRISTEN GPID SUMBERSARI DITINJAU DARI GAYA KOGNITIF FIELD INDEPENDENT: Analysis of Students’ Concept Understanding on Quadratic Equation Material at GPID Sumbersari Christian Junior High School in Terms of Field Independent Cognitive Style - Sriani, Niluh; Karniman, Tegoeh S.; M., Bakri; Hadjar, Ibnu (Aksioma, 2025)
This study is a descriptive study that uses qualitative approach aims to analyze students’ concept understanding on the quadratic equation material at GPID Sumbersari Christian Junior High School in terms of field independent cognitive style. Subjects in this study consisted of 3 students cognitive style field independent. The instruments in this study are GEFT test, concept understanding questions, and interview guidelines. Research results showed: the understanding of the three subjects of field independent cognitive style have not been able to state the concept of quadratic equation correctly. In giving examples and not examples of equations, subject 1 has not been able to examples and not examples correctly while subject 2 and subject 3 were able to give axamples and not examples of quadratic equations. Subject 3 were able to give examples and non-examples of quadratic equations well. Subject 1 and subject 3 have not been able to present the equation into mathematical representations correctly, while subject 2 was able to present the quadratic equation in the form of mathematical representations well. In using procedures or operations, subject 2 was able to use procedures well while subject 1 and subject 3 were not able to use procedures well. In linking concepts, the three subjects were still not able to relate concepts well. In this case the field independent cognitive style students do not fulfill all indicators of concept understanding so that students’ understanding in understanding the concept of quadratic equations is still low.